2022
DOI: 10.1093/burnst/tkac019
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional chitosan/gelatin@tannic acid cryogels decorated within situreduced silver nanoparticles for wound healing

Abstract: Background Most traditional wound dressings only partially meet the needs of wound healing because of their single function. Patients usually suffer from the increasing cost of treatment and pain resulting from the frequent changing of wound dressings. Herein, we have developed a mutifunctional cryogel to promote bacterial infected wound healing based on a biocompatible polysaccharide. Methods The multifunctional cryogel is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…In previous research, NYS has shown broad‐spectrum fungicidal activity and effectiveness against some fungal infections resistant to Amphotericin B, making it a desirable compound in topical patches [40] . NYS release in addition to TA would greatly benefit in wound healing which is why TA was not washed from the hydrogel [41–44] …”
Section: Resultsmentioning
confidence: 99%
“…In previous research, NYS has shown broad‐spectrum fungicidal activity and effectiveness against some fungal infections resistant to Amphotericin B, making it a desirable compound in topical patches [40] . NYS release in addition to TA would greatly benefit in wound healing which is why TA was not washed from the hydrogel [41–44] …”
Section: Resultsmentioning
confidence: 99%
“…87,88 It has been reported that the reduction of nuclear p65 may promote the conversion of heterodimer p65/ p50 into homodimer p50/p50, and the increased p50/p50 could assist in the transcriptional upregulation of IL-10, which promotes M2c macrophage polarization through the IL-10R/STAT3 signaling pathway. 89,90 He et al reported that a TA/Mg 2+ coating manipulated the adhesion and morphology of macrophages, inhibited M1 polarization, exerted an anti-inflammatory effect, and promoted M2 polarization. 91 Dong et al utilized TA to assemble red blood cells (RBCs) onto a Ti surface, conferring anti-biological contamination and immunomodulatory properties to the implants.…”
Section: Local Immunomodulatory Mechanism Of Mussel-inspired Adhesive...mentioning
confidence: 99%
“…Xu et al fabricated a AgNP-embedded chitosan-gelatin hydrogel (CS/Gel@TA/Ag) for both anti-infection and wound-healing purposes. 104 Tannic acid was introduced as a reducing agent for in situ AgNP preparation, as well as a protecting agent that delays the release of Ag + and prevents direct AgNP/cell contact. CS/Gel@TA/Ag hydrogels were found to be bactericidal against both S. aureus and E. coli by reducing TNF-α and scavenging excessive ROS.…”
Section: Hydrogel-based Strategy For Osteomyelitis Treatmentmentioning
confidence: 99%
“…The AgNP-alginate-dopamine hydrogel also exhibited significant inhibition zones against S. aureus and E. coli , while no inhibition zone was observed for the alginate-dopamine group. Xu et al fabricated a AgNP-embedded chitosan-gelatin hydrogel (CS/Gel@TA/Ag) for both anti-infection and wound-healing purposes . Tannic acid was introduced as a reducing agent for in situ AgNP preparation, as well as a protecting agent that delays the release of Ag + and prevents direct AgNP/cell contact.…”
Section: Hydrogel-based Strategy For Osteomyelitis Treatmentmentioning
confidence: 99%